Gambaran Kultur Bakteri dan Sensitivitas Antibiotik pada Pasien Sepsis di Rumah Sakit Ibnu Sina Periode 2019-2022 - Hidayati, Prema Hapsari; Danial, Nurul Fauziah; Mulyadi, Farah Ekawati; Yani Sodiqah; Hasta Handayani (Universitas Islam Negeri Alauddin Makassar, 2024)
Sepsis is a life-threatening organ dysfunction caused by an imbalance in the host's response to infection. This study aims to determine the description of bacterial culture and antibiotic sensitivity in sepsis patients at Ibnu Sina Hospital for the 2019-2022 period taken from medical record data. This study used a descriptive observational design with a retrospective approach based on secondary data from medical records at Ibnu Sina Hospital for the 2019-2022 period. Of the total 111 sepsis patients at Ibnu Sina Hospital for the 2019-2022 period, 89 samples were found with positive cultures and the most common bacteria found was Alkaligenes faecalis bacteria in 21 samples (23.6%) followed by Klebsiella sp. as many as 19 samples (21.3%) and Klebsiella pneumoniae as many as 12 samples (13.5%). The most sensitive antibiotics are levofloxacin and amikacin. It can be concluded that nosocomial infections with the most bacteria cause sepsis patients at Ibnu Sina Hospital are Alkaligenes faecalis (23.6%) and Klebsiella sp. (21.3%) which are gram-negative aerobic bacteria.